Drying and characterization of myrtle pulp - Regilane M. Feitosa; Rossana M. F. de Figueirêdo; Alexandre J. de M. Queiroz; Flávia C. dos S. Lima; Emanuel N. A. de Oliveira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to develop formulations of myrtle pulp with emulsifier/stabilizer (Emustab® and Super Liga Neutra®) in different proportions; characterize the best foam, based on density and over-run; and determine drying kinetics at temperatures of 50, 60, 70, 80 and 90 oC and thicknesses of 0.5, 1.0 and 1.5 cm. Incorporation of 1.5% Emustab® and 0.5% Super Liga Neutra® to the myrtle pulp (F1) proved to be effective for foam-mat drying. The addition of additives influenced the physicochemical parameters of the whole myrtle pulp. The Midilli et al. model showed the best fit to the experimental data.